ANALYSIS OF ITEM QUALITY IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS WITH RASCH MODELING - Evita, Evita; Sari, Eva Dwi Kumala; Susieni, Erni; Tamam, Badrud (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
The role of teachers in schools is expected, especially in evaluating student learning; teachers must pay attention to the quality of the items made. This study aims to determine the instrument's validity or the quality of the item's suitability with the model known as Item FIT (item suitability) on the End of Semester Assessment of Islamic Religious Education. The sample in this study was 216 respondents, using cluster random sampling. The results obtained; 1) the end-of-semester test given is categorized as easy when viewed from the level of student ability above the level of difficulty of the question; 2) the level of student ability is moderate with logit (0) producing very high information. Then, it will produce low information at the low or high ability level. It means that the PAI test produces maximum information when given to individuals with moderate ability. 3) Item fit criteria from 216 students, there are 93% that fit the model (fit model), and these students are said to fit the model because they have met at least two existing criteria; 4) The results of the analysis of the summary table above, 40 items analyzed there are 33 items (83%) that fit the model (fit model). 5) Reliability for Pearson reliability of 0.83 and item reliability of 0.97, it can be concluded that the consistency of student answers is good and the quality of the items in the PAI test is excellent reliability; 6) Gender bias analysis can be seen that 2 of the 40 items are DIF or need to be corrected because they harm certain gender groups.